2020
DOI: 10.1016/j.atmosenv.2020.117506
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific emission factors for Brazil increase the estimate of nitrous oxide emissions from nitrogen fertiliser application by 21%

Abstract: The use of synthetic nitrogen fertilisers is one of the most important land management practices proposed to improve crop and pasture productivity. The use of such fertilisers in excess can lead to greenhouse gas (GHG) emissions, linked to climate change, as well as ammonia (NH3) emissions, linked to eutrophication and soil acidification.. This context is especially important in Brazil, which is responsible for a significant share of the food produced in the world. To assess the impact of the use of nitrogen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The N 2 O-EF for the CN treatment was 1.02% which is very similar to the default value of 1% by IPCC Tier 1 [1]. Globally, the N 2 O-EF for N fertilizers ranged from 0.01% to 6.70%, and 75% of these EFs reported (or calculated) were in the range given by the IPCC for the Tier 1 default EF (0.30-3%, mean 1% [27]). Bouwman [32] analyzed the global values reporting that an average fertilizer-induced N 2 O emission is 1.25% ± 1% of N applied.…”
Section: Effect Of Fertilizer N Formulation On Annual Emission Factorsupporting
confidence: 68%
See 3 more Smart Citations
“…The N 2 O-EF for the CN treatment was 1.02% which is very similar to the default value of 1% by IPCC Tier 1 [1]. Globally, the N 2 O-EF for N fertilizers ranged from 0.01% to 6.70%, and 75% of these EFs reported (or calculated) were in the range given by the IPCC for the Tier 1 default EF (0.30-3%, mean 1% [27]). Bouwman [32] analyzed the global values reporting that an average fertilizer-induced N 2 O emission is 1.25% ± 1% of N applied.…”
Section: Effect Of Fertilizer N Formulation On Annual Emission Factorsupporting
confidence: 68%
“…Bouwman [32] analyzed the global values reporting that an average fertilizer-induced N 2 O emission is 1.25% ± 1% of N applied. A recent meta-analysis based on Brazilian cropland done by Mazzetto et al [27] reported the average N 2 O-EF was 1.12%, whereas a lower value was found when using AS (0.60%) fertilizer and a higher value from urea (1.45%) fertilizer. The N 2 O-EF for AS fertilizer presented by Mazzetto et al [27] is 42% higher than that of the present study.…”
Section: Effect Of Fertilizer N Formulation On Annual Emission Factormentioning
confidence: 99%
See 2 more Smart Citations
“…N 2 O coefficient was used to evaluate the percentage of N 2 O emission in fertilizers (Mazzetto et al, 2020 ):…”
Section: Methodsmentioning
confidence: 99%